Potential Impact of COVID-19 on the Indian Economy - 1Ashutosh Kumar Jha; Roshni Mehta (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Coronavirus outbreak was first reported in Wuhan, China on 31 December, 2019. Before reading in detail about the impact, first, let us study about coronavirus. The first case of the 2019–20 coronavirus pandemic in India was reported on 30 January 2020, originating from China. As of 13 April 2020, the Ministry of Health and Family Welfare have confirmed a total of 9,546 cases, 1146 recoveries (including 1 migration) and 335 deaths in the country. In the fight against Coronavirus, there's a global consensus of a first half 2020 recession worldwide. This could be true for India, potentially more so because of the larger informal nature of its economy, and the aggressive lockdown initiated. India will likely record its lowest-growth year ever. The Indian economy is expected to lose over Rs 32,000 crore (US$4.5 billion) every day during the 21-day-lockdown which was declared following the coronavirus outbreak. Up to 53% of businesses in the country will be affected. This paper is an attempt to know about the potential impact of COVID-19 on the Indian economy. Keywords: Economy, Central Banks, Chemical and Auto Industry.